2021
DOI: 10.1002/vms3.657
|View full text |Cite
|
Sign up to set email alerts
|

A field efficacy trial of a trivalent vaccine containing porcine circovirus type 2a and 2b, and Mycoplasma hyopneumoniae in three herds

Abstract: Background: This field trial was designed to evaluate the efficacy of a new trivalent vaccine containing porcine circovirus type 2a and 2b (PCV2a/b), and Mycoplasma hyopneumoniae at three independent locations. Methods: Three farms were selected based on their history of PCV2 and M. hyopneumoniae co-infection. Each farm housed a total of 60, 3-day-old pigs that were randomly allocated to one of three treatment groups. Pigs were administered the trivalent vaccine intramuscularly with either a 1.0 ml dose at 3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…Some authors have stated that it is preferable to establish the sow’s infection or vaccination history before vaccinating piglets at 3–4 weeks of age, as MDAs may interfere with the formation of vaccine-specific antibodies and reduce vaccine efficacy [ 21 , 22 , 23 , 24 ]. However, in our study, both IgG and NA antibodies increased in the experimental animals after vaccination, indicating that MDAs had no effect on vaccine efficacy, in agreement with what was reported by Um et al [ 25 ] and Kim and Hanh [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…Some authors have stated that it is preferable to establish the sow’s infection or vaccination history before vaccinating piglets at 3–4 weeks of age, as MDAs may interfere with the formation of vaccine-specific antibodies and reduce vaccine efficacy [ 21 , 22 , 23 , 24 ]. However, in our study, both IgG and NA antibodies increased in the experimental animals after vaccination, indicating that MDAs had no effect on vaccine efficacy, in agreement with what was reported by Um et al [ 25 ] and Kim and Hanh [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…Three main aspects make up the huge PCV2 flood. First, failure to vaccinate pigs with PCV2 leads to immune response suppression, which lowers overall production efficiency [ 18 ]. Second, it is extremely expensive to control and prevent PCV2 infection [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, later studies have found that vaccination against M. hyopneumoniae alone did not reduce PCV2-induced lesions [ 315 ]. Recently, bivalent (containing PCV2b and M. hyopneumoniae ) and trivalent vaccines (containing PCV2a/b and M. hyopneumoniae ) under experimental conditions were tested against dual infections (PCV2d and M. hyopneumoniae ), which successfully elicited effective protective immunity against concerned pathogens in the form of PCV2-specific neutralizing antibodies and PCV2- and M. hyopneumoniae -specific IFN-γ-SC [ 316 , 317 , 318 ]. Furthermore, trivalent vaccine mixture (3FLEX) was shown to be efficacious against a triple challenge of M. hyopneumoniae , PCV2, and PRRSV in pigs [ 319 ].…”
Section: Factors Associated With Clinical Manifestation Of Pcv-associ...mentioning
confidence: 99%